Dr. Fernando Dejo — Deep Plane Facelift — Lima - Dejo, Fernando (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Fernando Dejo, practicing in Lima, Peru. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002963; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; peru; lima